Economic impact of microfinance in Nepal: a case study of the Manamaiju Village Development Committee, Kathmandu - Adhikari, Dipak Bahadur; Shrestha, Jayanti (Economic Journal of Development Issues, 2015)
The concept of micro-credit was developed to mobilize small savings of poor people to create deposit, which may be accessible to unreachable and un-bankable poor, especially women. The study has highlighted that microfinance is an effective tool for bringing positive impact on the economic status of the respondents along with their family members. It has helped to generate extra income for their family and their own use. The extra income allows the respondents family to buy nutritious food, access to modern health care services and they can afford to send their children to the school. DOI: http://dx.doi.org/10.3126/ejdi.v15i1-2.11861 Economic Journal of Development Issues Vol. 15 & 16 No. 1-2, pp. 36-49